2020
DOI: 10.3389/fphar.2020.00012
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring TPE-CA Maintains Gut Microbiota and Bile Acids Homeostasis via FXR Signaling Modulation of the Liver–Gut Axis

Abstract: Antibiotics-induced changes in intestinal flora (dysbiosis) may have various effects on the host. Dysbiosis is associated with numerous metabolites including bile acids, which are produced in the liver from cholesterol and metabolized in the gut by intestinal microbiota. Total phenolic extracts of Citrus aurantium L. (TPE-CA) are rich in dietary flavanones and their glycosyl derivatives, including flavones, flavonols, polymethoxyflavones and coumarins, which exert positive health effects on the microbiota. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 48 publications
4
36
0
Order By: Relevance
“…This unbalanced condition, however, might be a precursor to MetS (Chávez‐Talavera, Tailleux, Lefebvre, & Staels, 2017; Saad, Santos, & Prada, 2016). A very recent study established an antibiotics‐induced mice model of dysbiosis, paralleled by BAs dysmetabolism and the intestinal dysfunction, to evaluate the metabolically modulatory effect of CFs in vivo (Liu et al., 2020). Results showed that the CFs‐rich extract from Citrus aurantium L .…”
Section: Protective Effects Of Cfs/metabolites On the Intestinal Barrmentioning
confidence: 99%
See 1 more Smart Citation
“…This unbalanced condition, however, might be a precursor to MetS (Chávez‐Talavera, Tailleux, Lefebvre, & Staels, 2017; Saad, Santos, & Prada, 2016). A very recent study established an antibiotics‐induced mice model of dysbiosis, paralleled by BAs dysmetabolism and the intestinal dysfunction, to evaluate the metabolically modulatory effect of CFs in vivo (Liu et al., 2020). Results showed that the CFs‐rich extract from Citrus aurantium L .…”
Section: Protective Effects Of Cfs/metabolites On the Intestinal Barrmentioning
confidence: 99%
“…counteracted the dysbiosis and recovered the intestinal permeability. This function of CFs was demonstrated to be associated with its capacity to reshape the homeostasis of BAs via up‐regulation of the liver‐gut axis related farnesoid X receptor (FXR)/fibroblast growth factor 15 (FGF15) pathway (Liu et al., 2020). FXR is a major BAs‐sensing receptor, whose activation leads to alterations in energy metabolism‐related pathways and therefore known as a key regulator of whole‐body energy metabolism (Teodoro, Rolo, & Palmeira, 2011).…”
Section: Protective Effects Of Cfs/metabolites On the Intestinal Barrmentioning
confidence: 99%
“…A previous study reported that the levels of bile acid were found to be low in carbon tetrachloride (CCl4) induced fatty liver rats (Zhang et al, 2019). When there is a disruption in the bile acid metabolism, it leads to a decrease in the activation of nuclear receptors such as FXR (farnesoid X receptor) and dysregulation in these receptors leads to NAFLD (Parséus et al, 2017;Chen et al, 2019;Liu et al, 2020). Chenodeoxycholic acid, muricholic acid and other cholic acids are primary bile acids produced in the liver as derivatives of cholesterol and secreted in the intestine as taurine and glycine conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…Liu (2020) [35] C57BL/6J mice Increase in ZO-1 and proteins associated with occludin and reduction in serum endotoxin. FXR stimulation with reduced hepatic synthesis of bile acids.…”
Section: Flavanonesmentioning
confidence: 99%